2016
DOI: 10.1016/j.jfda.2015.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Chemical quality evaluation of Antrodia cinnamomea fruiting bodies using phytomics similarity index analysis

Abstract: The fruiting body of Antrodia cinnamomea is used as a medicinal mushroom in Taiwan and is found on the inner cavity of the endemic species Cinnamomum kanehirai. In this study, phytomics similarity index (PSI) analysis was employed for the chemical quality evaluation of the A. cinnamomea fruiting bodies from different strains, and grown on various substrates. The results indicated that the different types of A. cinnamomea fruiting bodies contain eight index compounds, and that it was difficult to discriminate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Previous studies have pointed out that white and red AC have similar index components, including antcin A, antcin B, antcin C, antcin H, antcin K, dehydrosulfurenic acid, dehydroeburicoic acid, and 1,4-dimethoxy-2,3-methylenedioxy-5-methylbenzene (non-triterpenoid) [ 19 ]. In addition, consistent with previous studies, the content of total triterpenoids in the fruiting bodies of RAC was higher than WAC [ 19 , 20 ], while there is no literature report on the total triterpenoid content of YAC.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have pointed out that white and red AC have similar index components, including antcin A, antcin B, antcin C, antcin H, antcin K, dehydrosulfurenic acid, dehydroeburicoic acid, and 1,4-dimethoxy-2,3-methylenedioxy-5-methylbenzene (non-triterpenoid) [ 19 ]. In addition, consistent with previous studies, the content of total triterpenoids in the fruiting bodies of RAC was higher than WAC [ 19 , 20 ], while there is no literature report on the total triterpenoid content of YAC.…”
Section: Resultsmentioning
confidence: 99%
“…4 Mean body weight gain on the 28th day (g) = (28th − 21st)BW (g). 5 NC: negative control (olive oil). 6 Data are expressed as the mean ± SD (n = 5).…”
Section: Antimutagenicity Activitymentioning
confidence: 99%
“…Since the 1990s, more and more scientists have invested in the research of AC and its ingredients. More than one hundred different compounds have been isolated from AC, and the percentage of each compound may vary depending on different culture methods [ 5 , 6 ]. Most of the compounds belong to polysaccharides, benzenoids, diterpenes, triterpenoids, steroids, and maleic and succinic acid derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…As a mainstream form of complementary and alternative medicine, traditional Chinese medicine (TCM) has been widely accepted for cancer patients because of its beneficial effects and lack of serious side effects 3 . Antrodia cinnamomea is a rare fungus that grows in Taiwan, China, distributing over broad-leaved forests at an altitude of 200–2000 m. Pharmacological studies have shown that A. cinnamomea has anti-tumor, liver protection, immune regulation, inhibiting vascular neointimal formation, lowering blood pressure and cholesterol, inhibiting platelet aggregation, and other physiological activities 4 , 5 , 6 , 7 , 8 , 9 . Of the numerous functions, the effects of hepatoprotective especially anti-HCC were the most often reported.…”
Section: Introductionmentioning
confidence: 99%